PERAN TOKOH MASYARAKAT DALAM MENANAMKAN NILAI MORAL BERKELANJUTAN BAGI ANAK USIA SEKOLAH - Yadi, Yadi Samsul Hidayat; Elshap, Dewi Safitri (IKIP Siliwangi, 2024)
The fundamental element of a group is a character. Community figures, as we collectively understand them, are a group that can be used as a collective voice, or can be used as a place to gather and discuss problems faced by society. In this context we discuss individuals who are often referred to as representatives of the general public, such as heads of households, teachers, mosque imams, elderly people, and so on. These people may be able to provide constructive feedback. This is very influential for school-age children, especially in instilling sustainable moral values. Sustainable moral values are the moral values that underlie sustainable development. These values include environmental sustainability, social justice, and peace and harmony. Sustainable moral values are important to instill in every individual. This research uses qualitative methods with the following techniques: observation, documentation, and data collection through in-depth interviews. There are three methods used in data collection: data reduction, data presentation, and drawing conclusions. This research aims to examine the role of community leaders in instilling sustainable moral values in year-old children. Instilling sustainable moral values in school-aged children is a crucial issue in building the nation's next generation with character and responsibility for the environment. Community figures, as role models and opinion leaders in their environment, have an important role in this effort.